Efficacy of short-term antibiotic prophylaxis in immediate two-stage breast reconstruction after mastectomy: A retrospective monocentric study. Issue 8 (August 2021) - Barbera, Federico; Lisa, Andrea; Vinci, Valeriano; Maione, Luca; Veronesi, Alessandra; Giannasi, Silvia; Bandi, Valeria; Klinger, Francesco
Summary: Background: Infective complications following implant-based breast reconstruction range from 2, 5 to 24% and are often associated with high morbidity and poor outcome. Many authors still employ long-term antibiotic prophylaxis even though there is no conclusive evidence on the impact on infection-rate reduction. In the present study, we report we report our single-shot short-term prophylaxis protocol for surgical site infection prevention in immediate two-stage implant breast reconstruction. Methods: We retrospectively compared clinical data from two groups of women undergoing immediate two-stage breast reconstruction with tissue expander. Group 1 ( n = 391) was administered with long-term prophylaxis, and Group 2 ( n = 89) was administered with short-term prophylaxis associated with early drains removal (21 days maximum). We evaluated risk factors for infection, clinical preoperative data, time before drain removal, and clinical feature of the diagnosed infections (early or late onset) and compared the reconstructive outcome between the two groups (infection rate, implant loss rate). Results: We did not find any statistically significant difference in the infection rate (11, 51% overall) and implant loss rate (4, 49% overall) between the two groups. We found a difference in the implant loss to infection ratio (46.67% in group 1 and 20% in group 2, p < 0, 05) and in the time before drain removal (19 days in group 1 and 15 days in group 2, p < 0.001). We finally found an association between prolonged time before drain removal and increased infection rate ( p = 0.004). Conclusions: Short-term single-shot perioperative antibiotic prophylaxis associated with early drain removal (within 21 days postop) represents a safe approach in terms of prevention of local infective surgical complication and allows a more effective treatment of the diagnosed SSI.